Bridging the sustainability gap in rural health equity: policy evaluation and transnational lessons from Guizhou’s targeted medical assistance program - Kedi Sun (Frontiers in Public Health)
This study evaluated the sustainability of precision medical assistance policy in Guizhou Province through macro, meso and micro stakeholder analysis, combined with policy documents, statistical data and international comparison cases. The core objective is to identify barriers to long-term policy effectiveness and make evidence-based recommendations for improvement by drawing on global practice. This study used a three-tier stakeholder framework to analyze stakeholder dynamics at the macro level (national/local government), meso level (hospitals and medical teams in eastern Guizhou), and micro level (rural communities). Key findings reveal systemic sustainability challenges: at the macro level, unequal resource allocation and a “culture of dependency” on external assistance undermine local capacity building; At the meso-level, short-term personnel rotation (1–3 months on average), weak institutional management, and cultural mismatch (such as between the eastern team and Guizhou ethnic minorities) undermine service continuity; At the micro level, low policy awareness (due to poor communication in rural areas) and nonadherence to health behaviors (such as refusal to accept Western diagnoses in contrast to traditional practices) reduced the effectiveness of the intervention. Drawing on six decades of Chinese healthcare collaboration in Africa (with an emphasis on long-term capacity building and cultural integration) and Australia’s modified Monash Model (MMM) of rural talent retention (through hierarchical financial incentives and career pathways), the study proposes a three-dimensional framework: (1) local talent development (e.g., scholarship and rural career trajectories modeled on MMM); (2) Cross-regional collaboration for acculturation training (inspired by the pre-deployment immersion training for African medical teams); (3) culturally sensitive interventions (e.g., integration of traditional healers into primary care). These recommendations aim to provide actionable insights into health policy in resource-poor rural areas in China and globally, moving from short-term aid to strengthening sustainable local health systems.